PTU-061 Outcomes of paediatric liver transplant recipients following transition from paediatric to adult healthcare services. (28th May 2012) - Sagar, N; Leithead, J; Kelly, D; Adams, D; Arkley, J; Gunson, B; McKiernan, P; Smith, M; Lewis, P; Ferguson, J
Abstract : Introduction: Given the success of paediatric transplantation, there is now a growing population of patients that undergo transition from paediatric to adult healthcare services. In the renal transplant setting, these patients appear to be at increased risk of short-term graft loss. 1 However, the outcome of liver transplant patients who undergo transition remains unclear. Our aim was, therefore, to examine the patient and graft survival of liver transplant patients who undergo paediatric to adult healthcare transition. Methods: Single-centre retrospective study of 85 liver transplant recipients who underwent transition from paediatric to adult healthcare services between March 2001 and August 2011 (median follow-up time from transition 4.1 (range 0.2–10.7) years). Results: During the 10-year period, there were 48 (56.5%) males and 37 (43.5%) females. The median age at time of transplant was 8.4 (range 0.6–17.9) years. The initial indications for transplantation were: biliary atresia (27.1%), Wilson's (14.1%), other acute liver failure (11.8%), cystic fibrosis (9.4%), autoimmune hepatitis (8.2%), cryptogenic cirrhosis (4.7%), oxalosis (4.7%), other (20.0%). At the time of transition, the median age of the patients was 18.9 (range 16.6–23.1) years. 84.7% of patients were on their first graft, 12.9% were on their second and 2.4% were on their third at this point. The immunosuppression at transition was calcineurin inhibitor (CNI) monotherapy in 38.2%, a CNI combination regimen in 20.6%, and a CNI free regimen in 41.2%. Following transition, the estimated 1-, 5- and 10-year patient survival was 98.6%, 96.8% and 91.4%, respectively, and the estimated 1-, 5- and 10-year graft survival was 98.6%, 95.0% and 89.4%. Conclusion: Our results demonstrate that paediatric liver transplant recipients have a better outcome than previously reported in renal transplant recipients after transition. 1 This may suggest that this group of patients are more tolerant of their graft or that transition was adequately managed. Competing interests: None declared. Reference: 1. Watson AR . Non-compliance and transfer from paediatric to adult transplant unit. Pediatr Nephrol 2000;14 :469–72.